Asthma and hypercapnic respiratory failure. Issue 1 (March 2020) - Shamil, P.K.; Gupta, Nitesh; Agrawal, Sumita; Ish, Pranav; Chakrabarti, Shibdas
A 40-year-old, male non-smoker was diagnosed with asthma 6 years ago. He now presents with a 1-week history of worsening breathlessness with fever, cough, and purulent expectoration. He has had >10 emergency department visits and two admissions to hospital in the last 3 months. At each admission, he received bronchodilators and systemic steroids resulting in rapid improvement within 24 h. However, in the current presentation, the patient has no relief with corticosteroids and bronchodilators. His pulse is 140 per min, respiratory rate is 40 per min, blood pressure is 90/60 mmHg and room air oxygen saturation is 80%. Arterial blood gas (ABG) analysis shows hypercapnic respiratory failure. In view this respiratory failure, the patient is intubated and mechanical ventilation initiated. A chest radiograph is shown in figure 1. The therapy initiated includes bronchodilators, a systemic steroid, antibiotics and supportive care. Hypercapnia is an uncommon entity in asthma exacerbation. Meticulous evaluation for the underlying aetiology of hypercapnia is warranted in these patients. http://bit.ly/2sTKTk2